2022
DOI: 10.1021/acs.jctc.2c00083
|View full text |Cite
|
Sign up to set email alerts
|

A Bottom-Up Coarse-Grained Model for Nucleosome–Nucleosome Interactions with Explicit Ions

Abstract: The nucleosome core particle (NCP) is a large complex of 145–147 base pairs of DNA and eight histone proteins and is the basic building block of chromatin that forms the chromosomes. Here, we develop a coarse-grained (CG) model of the NCP derived through a systematic bottom-up approach based on underlying all-atom MD simulations to compute the necessary CG interactions. The model produces excellent agreement with known structural features of the NCP and gives a realistic description of the nucleosome–nucleosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 69 publications
(159 reference statements)
0
20
0
Order By: Relevance
“…For instance, although recent physics-based and ML potentials appear extremely promising, it remains challenging to accurately model hierarchical biomolecular structures without invoking elastic network or Go ̅ type potentials. 32,143 As suggested in Figure 1, bottom-up methods are often perceived as appetizing, but impractical approaches that require resources, capabilities, and experience that are not accessible to "non-expert" users. It is worth noting that almost ten years the pragmatic Martini model was already employed to study the organization of lipid membranes consisting of more than 60 distinct types of lipids.…”
Section: Emergent Challenges and Promising Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, although recent physics-based and ML potentials appear extremely promising, it remains challenging to accurately model hierarchical biomolecular structures without invoking elastic network or Go ̅ type potentials. 32,143 As suggested in Figure 1, bottom-up methods are often perceived as appetizing, but impractical approaches that require resources, capabilities, and experience that are not accessible to "non-expert" users. It is worth noting that almost ten years the pragmatic Martini model was already employed to study the organization of lipid membranes consisting of more than 60 distinct types of lipids.…”
Section: Emergent Challenges and Promising Directionsmentioning
confidence: 99%
“…It is worth noting that almost ten years the pragmatic Martini model was already employed to study the organization of lipid membranes consisting of more than 60 distinct types of lipids. 402 While Voth and co-workers recently employed bottom-up methods in developing a CG model for the coronavirus capsid 5 and Lyubartsev and co-workers recently developed a bottom-up model for nucelosomal self-assembly, 143 one may reasonably ask when�and for what systems�the…”
Section: Emergent Challenges and Promising Directionsmentioning
confidence: 99%
“…The nucleosome–nucleosome attraction could be regulated by the surrounding ion concentration. Sun et al began to simulate the effect of multivalent cations for systems comprising 20 nucleosome core particles, and the results of the coarse-grained (CG) model simulation revealed that the participation of positively-charged histone tails and multivalent (Mg 2+ , Co 3+ ) and monovalent (K + ) ions was necessary for DNA–DNA and core–core interactions and enabled the close stacking of nucleosomes [ 130 ]. Andreeva et al further compared the effects of Na + and K + ions on nucleosome structure, stability, and interactions with proteins.…”
Section: Multiple Regulatory Factors and Associated Mechanismmentioning
confidence: 99%
“… 12 , 13 The CHARMM force field is being used much less frequently, with an important exception of nucleosomes. 14 16 …”
Section: Introductionmentioning
confidence: 99%
“…Usually, the researchers choose the AMBER force field. This force field allows simulating complexes even with highly deformed DNA (with kinks as a result of protein intercalation), for example, in cases of Sox protein, Hbb, , Sac7d, LacI, and the others. , The CHARMM force field is being used much less frequently, with an important exception of nucleosomes. …”
Section: Introductionmentioning
confidence: 99%